2022
DOI: 10.1177/21582440221096447
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric and Gender Invariance Analysis of the Flourishing Scale in the Malaysian Context

Abstract: The Flourishing Scale is a new scale designed to measure psychological well–being. FS has been translated into more than 10 languages (e.g., Portuguese, Russian, Turki, Spanish, Egyptian, French, Chinses, Japanese, Malay, Urdu, and Persian). The psychometric analysis of the Flourishing Scale has not been explored in the Malaysian context. The aims of the current study were to examine the factor structure, reliability, concurrent validity (correlate with Satisfaction with Life Scale [SWLS] and Life Project Refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(56 reference statements)
2
5
0
Order By: Relevance
“…Conversely, FS scores showed a moderate negative correlation with negative affect, and strong and negative associations with depression, anxiety, stress, and general psychological distress. These results are likewise consistent with previous studies 15 - 23 , 25 , 26 , 29 , 31 - 36 and suggest that breast cancer patients with a higher level of flourishing tend to feel more satisfied with their lives in general, experience a greater sense of happiness and pleasure in life, cope better with adversity, value themselves more, and see the future with more hope. In addition, these women also show better psychological adjustment, expressing less general discomfort and generally feeling less irritable, anxious, sad or despondent.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Conversely, FS scores showed a moderate negative correlation with negative affect, and strong and negative associations with depression, anxiety, stress, and general psychological distress. These results are likewise consistent with previous studies 15 - 23 , 25 , 26 , 29 , 31 - 36 and suggest that breast cancer patients with a higher level of flourishing tend to feel more satisfied with their lives in general, experience a greater sense of happiness and pleasure in life, cope better with adversity, value themselves more, and see the future with more hope. In addition, these women also show better psychological adjustment, expressing less general discomfort and generally feeling less irritable, anxious, sad or despondent.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the reliability of FS scores, values of McDonald’s omega and Cronbach’s alpha (both .91) indicated that this was adequate, in line with previous research. 23 , 24 , 29 , 33 , 34 , 36 In general, the results show that the FS is a unidimensional measure of flourishing with satisfactory reliability in which high scores reflect a greater sense of competence, self-acceptance, optimism, and a greater contribution to the well-being of others.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Sci. 2024, 14, 366 2 of 12 scale was validated on various samples, especially teenagers [10,11] and students [12][13][14][15][16][17][18][19][20]. To our knowledge, the scale has not been validated in the Romanian language.…”
Section: Introductionmentioning
confidence: 99%